CEMENTO-OSSIFYING FIBROMA ON THE ANTERIOR MANDIBLE REGION: FIBROMA CEMENTO-OSSIFYING PADA REGIO DEPAN RAHANG BAWAH - Isnandar; Kasman Manullang; Hendro Sudjono Yuwono (Dentika: Dental Journal, 2011)
Cemento-ossifying fibroma (COF) is a rare benign tumor which mostly affects the mandible and the most common site is in the premolar-molar region . It is a painless, generally slow-growing, benign lesion which enlarges in an expansive manner. It is usually detected in the third and fourth decade of life and is more common in women. Radiographically, they appear as well-defined unilocular or multilocular intraosseous mass in the premolar- molar region of the mandible. The lesion is invariably encapsulated and with mixed radiolucent density. Its histopathology shows fibrous tissues with calcified structures resembling bone or cementum. This article reports a rare case of a-20-year old male with history of swelling in the anterior mandible region at tooth region 33-43 causing difficulty in occlusion. We have performed marginal resection and put AO plate crossing the bone defect. There was no wound dehiscence and exposed AO plate after six months of close observation. In conclusion, the mass has been succesfully excised and reconstructed using AOplate. Patient has been referred to the prosthodontic department for having a denture.